Ergonomic Studies on Safety and Health Work in the Industrial Building System (IBS) Project - Zailani, Muhamad Al Amin; Mohd Nawi, Nur Syazwani (Universiti Utara Malaysia, 2020)
Ergonomic in the construction industry is a priority for construction workers to produce high quality work, good health and good comfort. Therefore, the purpose of this study is to examine the workers’ awareness level, to identify the impact of ergonomic implementation and to investigate the strategies to improve ergonomic implementation on the safety and health work for workers in the Industrial Building System project in Perlis. This study is conducted by using qualitative research method, where the data is collected through semi-structured interview. The three respondents are the top management of the construction in Perlis. The results of this study revealed that the workers’ awareness level is high because of various steps have been taken by the government to put more important of ergonomic to the workers in the construction industry and knowledge of ergonomics within construction workers to reduce injuries or accidents in the site of the construction. The impact of ergonomics gives the workers more comfortable doing work under high pressure, reduce injuries, give the best result for the quality of work, taking care of the health, gives workers a greater sense of accomplishment and the time to complete the project can be adjusted at the appointed time as there are no accident or injuries during work.